A self–adaptive resource index and discovery system in distributed computing environments. (31st July 2012) - Chung, Wu–Chun; Lin, Yi–Hsiang; Lai, Kuan–Chou; Li, Kuan–Ching; Chung, Yeh–Ching
Resource–sharing systems apply the Peer–to–Peer (P2P) technique to provide scalable multi–attribute range queries. However, due to the heterogeneity of resources and the variation of sharing policies from different providers, current P2P–based resource discovery systems may suffer the load imbalance problem in large–scale distributed systems. In this paper, a self–adaptive resource index and discovery system, NAMED SARIDS, is proposed to achieve load balancing in distributed computing environments, by adopting a two–tier architecture based on structured P2P overlay. Experimental results show that SARIDS is scalable yet efficient for load balancing even in non–uniform peer range environments.